A Semiotic Analysis of L’ORÉAL Advertisement: This is an Ad for Men Campaign - Ariani, Ni Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This study aims to analyze the message in an advertisement by applying the theory of semiotics. The data source in this study is one of the advertisements from L'Oreal’s campaign, entitled “This is an Ad for Men Campaign.” The theory utilized as a reference in the analysis process is the semiotic theory proposed by Chandler (2017) by paying attention to the two forms of signs contained in the advertisement, namely verbal sign and visual sign. The data collection method in this study is a combination of the observation method with the note taking technique. While the qualitative method is applied in the process of analyzing the data proposed by Creswell (2009). In presenting the results of the analysis, this study combines formal method in the form of using tables and photo as well as informal methods in the form of descriptions. The conclusion of this study is that this advertisement does not only promote their products for commercial purposes only, but this advertisement is also able to raise social issues experienced by women both in their personal lives and in their professional careers. This advertisement combines the power of verbal sign and visual sign in conveying their message to a wide range of audiences. Three verbal signs and three visual signs are combined to obtain the audiences’ attention in understanding the message of this advertisement.